BSA Immobilization on QCM Sensor with Hydrophobic-Hydrophilic Properness Modification of Polystyrene Surface Using Ultraviolet (UV) Radiation - Fenny Irawati; Setyawan P. Sakti; Unggul P Juswono; Aulanni’am Aulanni’am (Natural B, Journal of Health and Environmental Sciences, 2013)
Research has been done to improve the optimization of the BSA (Bovine Serum Albumin) immobilization process on QCM sensor by modifying the nature of the hydrophobic-hydrophilic polystyrene surfaces using ultraviolet radiation (UV). The silver electrode of QCM sensor coated with a solution of polystyrene using spin coating technique. Sensor with polystyrene coating was heated using an oven until it reaches a temperature of 200 °C and then irradiated with ultraviolet light. A 30 µL of distilled water was dropped on the sensor surface and the formed contact angle was observed. The observation of the contact angle showed that there was a change in the nature hydrophobicity of sensor surface irradiated with UV. BSA immobilization was done by injecting a certain amount of BSA concentration in PBS solution on top of the sensor. We found that best surface for immobilization of BSA is one which is without UV irradiation. This means that the immobilization is mainly caused by hydrophobic force.